Do Determinants of Behaviors Influence the Intention to Invest in Green Sukuk? - M Iqbal Affandi; Farida Rahmawati (Jurnal Ekonomi Syariah Teori dan Terapan, 2023)
ABSTRACT Green finance is being developed in response to growing environmental concerns. Green sukuk is a type of green finance based on Shariah rules. Green sukuk initiatives have been carried out in Indonesia since 2019. The participation of green sukuk has been consistently increasing every year. This study aimed to determine the cause of this occurrence using green financing knowledge, environmental concern, risk behavior, financial literacy, and intention as observed variables. This research was based on a quantitative method using primary data. The sampling technique used in this study was convenience sampling and 10 times rule for SEM. Data was collected by distributing structured questionnaires to approximately 176 respondents. The respondents came from individuals aged between 20-40 years old, from different educational backgrounds, and from different regions in Indonesia. The results of the structural equation modeling analysis show that green finance knowledge significantly influences intention, while environmental concern and risk behavior significantly influence financial literacy. Financial literacy as a moderating variable has a significant influence on intention. The findings are expected to guide the development of effective marketing strategies for green sukuk to attract investors. Keywords: Green Sukuk, Behavior, Intention, Financial Literacy   ABSTRAK Bentuk dari kepedulian terhadap lingkungan untuk mengatasi masalah ini adalah dengan pengembangan green finance. Salah satu bentuk dari green finance yang menerapkan prinsip syariah adalah green sukuk. Inisiatif green sukuk telah dilakukan di Indonesia sejak tahun 2019. Tingkat partisipasi green sukuk terus meningkat setiap tahunnya. Tujuan dari penelitian ini adalah untuk memahami faktor di balik fenomena ini. Pendekatan yang digunakan adalah kuantitatif dengan data primer. Teknik sampling yang digunakan dalam penelitian ini adalah convenience sampling dan metode 10 times rule untuk SEM. Pengumpulan data dilakukan dengan membagikan kuesioner terstruktur kepada 176 responden. Responden terdiri dari individu berusia 20-40 tahun, dari beberapa latar belakang pendidikan berbeda, dan dari beberapa wilayah di Indonesia. Dengan bantuan analisis Structural Equation Modelling, hasil dari penelitian ini menunjukkan bahwa green financing knowledge berpengaruh signifikan terhadap minat, sedangkan environmental concerns dan risk behavior berpengaruh signifikan terhadap literasi keuangan. Literasi keuangan sebagai variabel moderasi berpengaruh signifikan terhadap minat. Hasilnya diharapkan dapat memandu pengembangan strategi pemasaran sukuk hijau yang efektif untuk menarik investor. Kata Kunci: Green Sukuk, Perilaku, Minat, Literasi Keuangan